Extraction of collagen from bullfrog skin - Pua, Li Yu (Nanyang Technological University, 2020)
Food wastage is a growing issue in recent years, putting a huge burden on the environment and economy. Often, these food wastes have high organic content and are good natural resources. One such example is collagen. Collagen is the most abundant protein in our body and is usually found in connective tissues that make up several body parts such as tendons, ligaments and skin. It provides our skin with structurality and strengthens our bones. There are four types of collagen – Type I, Type II, Type III and Type IV. 90% of human body is made up of Type I collagen which is composed of densely packed fibres. Due to the use of collagen in biomedical applications such as wound dressing, collagen extraction has been researched extensively in recent years. Mammalian sources such as bovine and porcine are the most common sources of collagen for commercial use. However, there is a risk of disease transmission and religious issues involved with using mammalian derived collagen. An alternative will be extracting collagen from bullfrog skin. Collagen derived from bullfrog skin is safer and does not have religious restrictions. Furthermore, as bullfrog skins are usually disposed since they are not consumed, extraction of collagen from bullfrog skins helps to minimise food wastes. In this project, the traditional acid solubilisation method was used to extract collagen from bullfrog skins and different types of acids – Malic acid, citric acid and tartaric acid were used to investigate if the type of acid used will affect collagen extraction.